Autocrine Production of PDGF Stimulated by the Tenascin-C-Derived Peptide TNIIIA2 Induces Hyper-Proliferation in Glioblastoma Cells - Fujita, Motomichi (Int J Mol Sci, 2019)
Expression level of tenascin-C is closely correlated to poor prognosis in glioblastoma patients, while the substantial role of tenascin-C responsible for aggressive progression in glioblastoma cells has not been clarified. We previously found that peptide TNIIIA2, which is derived from the tumor-associated tenascin-C variants, has the ability to promote cell adhesion by activating β1-integrins. Our recent study demonstrated that potentiated activation of integrin α5β1 by TNIIIA2 causes not only a dysregulated proliferation in a platelet-derived growth factor (PDGF)-dependent manner, but also disseminative migration in glioblastoma cells. Here, we show that TNIIIA2 enhances the proliferation in glioblastoma cells expressing PDGF-receptorβ, even without exogenous PDGF. Mechanistically, TNIIIA2 induced upregulated expression of PDGF, which in turn stimulated the expression of tenascin-C, a parental molecule of TNIIIA2. Moreover, in glioblastoma cells and rat brain-derived fibroblasts, tenascin-C upregulated matrix metalloproteinase-2, which has the potential to release TNIIIA2 from tenascin-C. Thus, it was shown that autocrine production of PDGF triggered by TNIIIA2 functions to continuously generate a functional amount of PDGF through a positive spiral loop, which might contribute to hyper-proliferation in glioblastoma cells. TNIIIA2 also enhanced in vitro disseminative migration of glioblastoma cells via the PKCα signaling. Collectively, the tenascin-C/TNIIIA2 could be a potential therapeutic target for glioblastoma.